Pemikiran Ibnu Miskawaih Tentang Pendidikan Islam Dan Relevansinya Dengan Dunia Modern - Shofiyah, Nida; Siregar, Maragustam (Halaqa: Journal of Islamic Education, 2025)
Islamic education is currently challenged by the many problems of the younger generation, especially with regard to moral relationships with Allah SWT, themselves and fellow humans. The purpose of this research is to analyze Ibn Miskawaih's thoughts on Islamic Education and its relevance to the modern world. This research uses a qualitative approach and literature study method. Based on the results of the research, morals in humans have a close relationship with the soul. The soul has three powers, namely thinking power (rationality), anger power, and desire power. This power is a provision for humans to do good or bad. Ibn Miskawaih offers a way for humans to produce noble and superior morals in the view of Islam, namely with the concept of “middle way”. Departing from Ibn Miskawaih's thoughts on moral philosophy, there is an analysis of the perspective of Islamic education in various aspects, including aspects of moral education goals, moral education materials, educators and students, educational environment, and educational methods. Ibn Miskawaih's thinking until now has a strong relevance so that it can be implemented in the world of modern Islamic Education.